2021
DOI: 10.3390/jcm10194466
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonalcoholic Fatty Liver Disease (NAFLD) with Peripheral Diabetic Polyneuropathy: A Systematic Review and Meta-Analysis

Abstract: Aims. The relationship between nonalcoholic fatty liver disease (NAFLD) and diabetic polyneuropathy (DPN) has been demonstrated in many studies, although results were conflicting. This meta-analysis aims to summarize available data and to estimate the DPN risk among NAFLD patients. Materials and methods. We performed a comprehensive literature review until 4 June 2021. Clinical trials analyzing the association between NAFLD and DPN were included. Results. Thirteen studies (9614 participants) were included. DPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
(72 reference statements)
3
4
0
Order By: Relevance
“…At variance with those studies [ 22 , 24 ], however, we found no association between FLI and DR or DSP. Therefore, our findings are more in line with those of a recent meta-analysis showing increased DSP prevalence in subjects with type 2 diabetes with NAFLD, but not in those with type 1 diabetes [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…At variance with those studies [ 22 , 24 ], however, we found no association between FLI and DR or DSP. Therefore, our findings are more in line with those of a recent meta-analysis showing increased DSP prevalence in subjects with type 2 diabetes with NAFLD, but not in those with type 1 diabetes [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…[35][36][37] As a result, imaging modalities such as ultrasound are commonly used as a first-line diagnostic step in evaluating hepatic steatosis, owing to its safety, availability, and low cost. 38 According to Greco et al 39 it is evident that diabetic patients should have a hepatic ultrasonography examination to detect NAFLD early.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] Insulin resistance could also play a part in the development of peripheral neuropathy, explaining why it is so common in people with pre-diabetes 42 and why insulin sensitisers, such as metformin and thiazolidinediones, could decrease the occurrence of diabetic peripheral neuropathy compared to insulin or insulin secretagogues, after adjusting for differences in glycemic control. 47 A meta-analysis study by Greco et al 39 They showed that DPN prevalence was significantly higher in T2DM patients with NAFLD. This could be because of not limiting the NAFLD diagnosis method to ultrasonography, as they included studies using ultrasound, composite noninvasive biomarkers, or ultrasound elastography for NAFLD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a significantly increased prevalence of DPN in T2DM with Nonalcoholic Fatty Liver Disease (NAFLD). 31 This may be related to the fact that patients with NAFLD have enhanced pro-inflammatory and pro-atherosclerotic effects. Both ALB and FIB selected for this study are produced by the liver, and the combination of the two amplifies the inflammatory response in the body and is a more sensitive indicator of response to inflammation.…”
Section: Discussionmentioning
confidence: 99%